Identifikasi Jalur Sesar Aktif Menggunakan Analisis First Horizontal Derivative (FHD) dan Second Vertical Derivative (SVD) pada Data Gravitasi - Ismoyo W, Tri; Adhi, M.Aryono; Syirojudin, M.; Sania, Ismi Rohmatus; Hasanuddin, Hasanuddin; Islam Masruri, Fakhrul (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to delineate and characterize active fault lines in Sumedang Regency, West Java, which exhibits significant geological complexity resulting from the convergent tectonic processes between the Indo-Australian and Eurasian Plates, as well as its proximity to prominent regional fault systems such as the Lembang Fault. The investigation utilized the gravity method combined with derivative analysis to identify subsurface fault structures that potentially contribute to seismic hazards. Gravity data were collected using a Scintrex CG-6 gravimeter with an accuracy of 0.01 mGal, supplemented by the global gravity model GGMPlus and SRTM topographic data. The Complete Bouguer Anomaly (CBA) map was processed through First Horizontal Derivative (FHD) and Second Vertical Derivative (SVD) filtering techniques to enhance fault detection capability. Results from data processing and interpretation reveal linear patterns and anomaly points characterized by high FHD values and significant SVD anomalies along several cross-sectional lines. These patterns indicate the presence of active fault zones that align with regional geological trends and the distribution of seismic activity following the earthquakes at the end of 2023. This study concludes that the integration of the FHD and SVD methods on gravity data is effective in identifying active fault lines. The findings can serve as a fundamental basis for geological disaster mitigation and safer regional spatial planning.   Keywords: Gravity, FHD, SVD, Bouguer Anomaly, Active Fault